Stability analysis of bi-directionally corrugated steel plates with orthotropic plate model. (1st April 2018) - Gajdzicki, Michał; Perliński, Wojciech; Michalak, Bohdan
Highlights: The stability of the bi-directionally corrugated plates under compression and shear is analyzed. Averaging procedures leading to equations with constant coefficients is presented. The corrugated plates are replaced by a equivalent orthotropic plate model. The averaged stiffness modules for orthotropic plate model was determined. The proposed model was validated by comparing the critical force values. Abstract: The aim of this paper is the investigation focused on sinusoidally corrugated in both direction steel plates. The analyzed plates can be used as corrugated webs in cold-formed steel profiles, and then eliminate the need for transverse stiffeners. The stability analysis of the bi-directionally corrugated plates under compression and shear requires the use of shell model. In case of dense corrugation, that model is described by differential equations with strongly oscillating coefficients. The use of such equations in the analysis of engineering issues is very troublesome, even when using finite element method. This work presents one of the averaging procedures leading to equations with constant coefficients, in which the corrugated plates are replaced by a certain equivalent continuous structure with mean stiffness modules that describe the properties of the actual plate. The aim of the study is to demonstrate the possibility of using an orthotropic plate model for the analysis of the stability of this type of steel panels. The averaging effective modules for the orthotropic model has been identified. The proposed model was validated by comparing the critical force values obtained from the orthotropic plate model and the FEM shell model. The proposed procedures only takes into account linear elastic behavior of the material.